2013
DOI: 10.1155/2013/152052
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine and Alanyl-Glutamine Increase RhoA Expression and ReduceClostridium difficileToxin-A-Induced Intestinal Epithelial Cell Damage

Abstract: Clostridium difficile is a major cause of antibiotic-associated colitis and is associated with significant morbidity and mortality. Glutamine (Gln) is a major fuel for the intestinal cell population. Alanyl-glutamine (Ala-Gln) is a dipeptide that is highly soluble and well tolerated. IEC-6 cells were used in the in vitro experiments. Cell morphology was evaluated by atomic force microscopy (AFM) and scanning electron microscopy (SEM). Cell proliferation was assessed by WST-1 and Ki-67 and apoptosis was assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…By contrast, actin disruption alone, another well-known consequence of TcdA, by latrunculin A was not sufficient to mimick the observed apoptotic effects 72 . TcdA-induced apoptosis could be reversed by co-incubation with glutamine or alanyl-glutamine in IEC-6 cells that was accompanied by increased RhoA expression 73 . Additionally, other pathogens such as Escherichia coli, Mycobacterium avium or Salmonella typhimurium have been shown to exploit mechanisms involving RhoA activation to facilitate infection 74 - 77 .…”
Section: Introductionmentioning
confidence: 80%
“…By contrast, actin disruption alone, another well-known consequence of TcdA, by latrunculin A was not sufficient to mimick the observed apoptotic effects 72 . TcdA-induced apoptosis could be reversed by co-incubation with glutamine or alanyl-glutamine in IEC-6 cells that was accompanied by increased RhoA expression 73 . Additionally, other pathogens such as Escherichia coli, Mycobacterium avium or Salmonella typhimurium have been shown to exploit mechanisms involving RhoA activation to facilitate infection 74 - 77 .…”
Section: Introductionmentioning
confidence: 80%
“…In respect of the role of Rho proteins in the toxicity of C. difficile toxins, transfection of Rho GTPases decreases the sensitivity of host cells to TcdB [ 73 , 126 ], while supplementation of glutamine and alanyl-glutamine to TcdA treated cells can increase RhoA expression and then reduce the intestinal epithelial cell damage [ 127 ]. Although ADP-ribosylation or phosphorylation of Rho proteins has not been observed in TcdB intoxicated intact oocytes [ 128 ], the protective role of phosphorylation of Rho proteins in TcdA and TcdB intoxicated cells has been reported [ 129 , 130 ].…”
Section: Conclusion and Future Considerationsmentioning
confidence: 99%
“…Santos et al . additionally showed in IEC‐6 cells that alanyl‐glutamine treatment reduced TcdA toxin damage and increased RhoA expression, suggesting a potential explanation for the protective effects . Using intestinal loop models, Warren et al .…”
Section: Areas For Improvement and Targets For Emerging Therapiesmentioning
confidence: 98%
“…106 Santos et al additionally showed in IEC-6 cells that alanyl-glutamine treatment reduced TcdA toxin damage and increased RhoA expression, suggesting a potential explanation for the protective effects. 107 Using intestinal loop models, Warren et al showed that treatment with ATL 370 (an adenosine A2A receptor agonist) and alanyl-glutamine reduced ileal secretions, apoptosis, mucosal injury, and levels of KC and IL-10 after C. difficile toxin A exposure. 108 A phase II clinical trial (NCT02053350) testing the efficacy of alanyl-glutamine as a supplement (44 g orally daily for 10 days) during treatment of CDI was terminated due to low enrollment.…”
Section: Treatment Of Primary Cdi: Reducing Severity and Increasing Cmentioning
confidence: 99%